3D-Printed Accessories and Auxiliaries in Orthodontic Treatment - Marcel Paľovčík; Juraj Tomášik; Márton Zsoldos; Andrej Thurzo (Applied Sciences)
The integration of 3D printing has transformed orthodontics, allowing for the creation of highly customized intraoral devices that support traditional orthodontic treatments. This review examines the innovations and applications of 3D-printed accessories in orthodontics, focusing on customization, precision, and workflow improvements. In-office 3D printing enables reduced dependence on external labs, enhancing efficiency and potentially lowering costs. Key topics include material properties, biocompatibility, and clinical applications, alongside an evaluation of both successes and limitations highlighted in recent studies. Unlike prior research focused on aligners and braces, this review centers on auxiliary devices, demonstrating how 3D printing can revolutionize these less-studied accessories in orthodontics. The rise of 4D memory shape materials signals a potential breakthrough in “smart orthodontics”, where directly printed devices can adapt over time. This innovation could lead to a new era of personalized dynamic orthodontic solutions with 3D-printed auxiliaries, providing unprecedented customization and expanding the scope of orthodontic care. Further research is essential to address challenges related to durability, biocompatibility, and long-term clinical performance to optimize 3D printing’s role in orthodontic treatments.